Otimização de processos de produção em uma empresa de manutenção predial com base na produção mais limpa - Corazza, Cristyan Ricardo (2019)
As the buildings that have been used are under construction, expressive volumes of materials are being wasted in the form of Civil Construction Waste, called RCC. These are the processes of obsolete, flawed and wasteful. The present study aimed to reduce the generation of waste and environmental impact in companies that have maintenance and maintenance works. Metallic Finances of Production More CONAMA nº 307/2002. For the monitoring of results, the monitoring and execution of the civil construction works, besides the stages of planning and execution of the services. The study identified which are the most relevant services using the frameworks of ABC inputs. In the services being selected through Leopold's matrix the relevance and magnitude of the environmental impacts. And after realizing an elaboration of an implementation plan of continuous improvement, the company was applied in an application in its construction sites. The elaborated implementation plan was a process of decision making on the changes of performance, processes and routines of the construction site realizing an investment of the outstanding opportunities. As development options, those that have become tougher and more advantageous have been improved, such as: replacement of primary ingredients, technical training, and implementation of efficient planning. Clearly, it is possible to adapt ad hoc adaptations to already consolidated services.